PENGARUH LAYANAN KLASIKAL TERHADAP CARA BELAJAR YANG EFEKTIF PADA SISWA KELAS VIII DI MTs TARBIYATUL HUDA JENGGAWAH JEMBER - Moh. Anas Faruq (FKIP Universitas Islam Jember, 2014)
The influence of classical serve to method of effective studi for grade student VIII of MTs Tarbiyatul Huda Jenggawah Jember in academic year 2013/2014. Classical serve is one of konselor program by scheduled come in the clases, which materi about ke-BK-an, the one mean how methode effective studi. The mean of research is see influence of classical serveto method of effective studi, With respondent that researcherd as many as 50 student from 90 student grade VIII take random sampling. Methode that used in research is questionnaire methodes observasion, documentation. Analysis with using formula chi squaer with looking for statistic of coefition contigention. Based on result of research. So chi square result X² = 4,562 for significan grade 95% = 3,84. After consulted at table coefision contingention so calculation bigger then chi squaretable. That mean conection. With thus achived conclusion: the existence conection classical serve with methode efectif studis at student of MTs Tarbiyatul Huda in the academic year 2012/2013 and the conection is low. Key words : Clasical serve and method of efective studi